Histological and immunohistochemical characterization of granulomas in alpacas (Vicugna pacos) naturally infected with tuberculosis - Agulló-Ros, Irene; Ruedas-Torres, Inés; Hunter, Laura; Bird, Alison; Whitehead, Claire E.; Salguero, Francisco J. (Frontiers in Veterinary Science, 2025)
Tuberculosis (TB), caused by the Mycobacterium tuberculosis complex (MTBC), is a chronic zoonotic disease of increasing concern in alpacas (Vicugna pacos), a species highly susceptible to the disease. Given the growing alpaca population in Europe and zoonotic potential, understanding TB pathology in alpacas is crucial. This study provides the first comprehensive histopathological and immunohistochemical characterization of TB lesions in naturally infected alpacas. Granulomas from the lungs (n = 175), liver (n = 241), and lymph nodes (n = 55), were classified into four developmental stages (I, II, III and IV) based on their morphology, necrosis, fibrosis, cellular composition, and presence of acid-fast bacilli (AFBs). Advanced granulomas (stages III and IV) predominated in all tissues, indicating chronic infection. High numbers of AFBs were observed in lung and lymph node granulomas across all stages, with very rare presence of multinucleated giant cells (MNGCs). This pattern in the lung, with extensive necrosis and lack of fibrous encapsulation, together with the presence of abundant AFBs, suggests deficient immune control and significant transmission risk. In contrast, liver granulomas, particularly encapsulated stage IV lesions, showed fewer detectable AFBs, implying better mycobacterial control in this organ. Immunohistochemistry in selected granulomas revealed ionized calcium-binding adaptor protecin (IBA1) immunopositive macrophages were most prevalent cells in early stages (stage I and II), while T (CD3+) and B lymphocytes (B-cell specific activator protecin+) increased in advanced (stage III and IV) granulomas, forming peripheral lymphoid follicle-like structures. Neutrophils (immunopositive to myeloperoxidase) were less abundant, but more prominent in advanced lesions showing extensive necrosis. The high incidence of liver lesions suggests high dissemination of pathogenic mycobacteria and generalized tuberculosis in this species. This research fills knowledge gaps about tuberculous granulomas in camelids and highlights alpacas as potential sources of mycobacterial excretion, posing a transmission risk to domestic animals, wildlife, and humans.